The Influential Principles in Problem-Based Learning: A Systematic Review on English Language Learning - Aryanti, Nurul; Anggaira, Aria Septi; Ardiansyah, Welly; Suhono, Suhono (JOLLT Journal of Languages and Language Teaching, 2024)
Since the beginning of its application, the Problem-Based Learning (PBL) has been recognized for its success in improving the quality of learning in various disciplines from different countries. Then, it has been recommended to be applied in all levels of education, especially in higher education. Therefore, this review is aimed at exploring the most influential principles of PBL which give contribution to the success of the learning outcome in English language learning. This review was compiled based on the guideline from PRISMA (Preferred Reporting Items for systematic reviews and Meta-Analysis). Data was searched and collected from studies published from electronic data bases of reputable international journals issued from 2012 to 2020. From 105 articles in the same area of English language learning, 7 articles were chosen to match the purpose of this review. The 7 articles have the same research methodology (experimental study), in which the discussions of the articles are analyzed to find the most influential principles supporting the success of PBL for all level of education in English language learning. It was found that PBL has proven to be effective in English language learning for all levels of education. In addition, the review shows that all discussions of the articles state that there are five most influential principles of the PBL that give contribution to the success of the language learning, the incorporation of ill structured/real life problems, a student-centered approach, collaborative learning, problem solving, and critical thinking.